Given the sequence 7, 14, 28, 56, ..., which expression shown would give the tenth term?

Question

Asked 10/16/2013 11:25:09 AM

Updated 11/3/2014 8:52:02 PM

10 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/3/2014 8:52:02 PM]

conconn|Points 90|

matahari|Points 2630|

emdjay23|Points 2538|

rio8408|Points 400|

rio8408|Points 400|

rio8408|Points 400|

chumz|Points 140|

eitak1987|Points 55|

eitak1987|Points 55|

bongche|Points 3864|

eturker|Points 3037|

Question

Asked 10/16/2013 11:25:09 AM

Updated 11/3/2014 8:52:02 PM

10 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/3/2014 8:52:02 PM]

Rating

0

If the sixth term of a sequence is 128 and the common ratio is 2, then the first term is 4 .

Let the first term is a

128 = a*2^(6 - 1)

128 = a*32

a = 128/32

a = 4

Let the first term is a

128 = a*2^(6 - 1)

128 = a*32

a = 128/32

a = 4

Added 11/3/2014 8:38:26 PM

0

The seventh term of a sequence whose first term is 1 and whose common ratio is 3 is 729 .

Seventh term = 1*3^(7 - 1) = 3^6 = 729

Seventh term = 1*3^(7 - 1) = 3^6 = 729

Added 11/3/2014 8:40:07 PM

0

The tenth term for the given the sequence 7, 14, 28, 56, is 7*2^9.

Common ratio = 56/28 = 28/14 = 14/7 = 2

Tenth term = 7*2^(10 - 1) = 7*2^9

Common ratio = 56/28 = 28/14 = 14/7 = 2

Tenth term = 7*2^(10 - 1) = 7*2^9

Added 11/3/2014 8:42:36 PM

0

(-4a^3)^3·a^4

= -64 a^9*a^4

= -64a^13

= -64 a^9*a^4

= -64a^13

Added 11/3/2014 8:44:28 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/3/2014 9:03:27 PM]

0

The fifth term of a sequence whose first term is 5 and whose common ratio is 3 is 405 .

Fifth term = 5*3^(5 - 1) = 5*3^4 = 405

Fifth term = 5*3^(5 - 1) = 5*3^4 = 405

Added 11/3/2014 8:45:31 PM

0

The next term of the following sequence 25, 10, 4, ... is 8/5 .

Common ratio = 4/10 = 10/25 = 2/5

Next term = 4*2/5 = 8/5

Common ratio = 4/10 = 10/25 = 2/5

Next term = 4*2/5 = 8/5

Added 11/3/2014 8:47:44 PM

0

(y^3)^5 · y^4

= y^15*y^4

= y^19

= y^15*y^4

= y^19

Added 11/3/2014 8:48:28 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/3/2014 9:00:48 PM]

0

(-3ab^3)^4

= 81a^4b^12

= 81a^4b^12

Added 11/3/2014 8:49:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/3/2014 9:02:27 PM]

0

x^8 ÷ x^4 · x^2

= x^4*x^2

= x^6

= x^4*x^2

= x^6

Added 11/3/2014 8:49:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/3/2014 9:04:29 PM]

0

23 ÷ 52

= 23/52

= 0.4423076923

The answer for 23/52 is about 0.44 .

= 23/52

= 0.4423076923

The answer for 23/52 is about 0.44 .

Added 11/3/2014 8:51:57 PM

27,673,834

questions answered

There are no comments.